Alleviation of Brain Injury-Induced Cerebral Metabolic Depression by Amphetamine: A Cytochrome Oxidase Histochemistry Study - Richard L. Sutton; David A. Hovda; Michael J. Chen; Dennis M. Feeney (Neural Plasticity)
Measurements of oxidative metabolic capacity following the ablation of rat sensorimotor cortex and ,he administration of amphetamine were examined to determine their effects on the metabolic dysfunction that follows brain injury. Twenty-four hours after surgery, rats sustaining either sham operations or unilateral cortical ablation were administered a single injection of D-amphetamine (2 mg/kg; i.p.) or saline and then sacrificed 24 h later. Brain tissue was processed for cytochrome oxidase histochemistry, and 12 bilateral cerebral areas were measured, using optical density as an index of the relative amounts of the enzyme. Compared with that of the control groups, cytochrome oxidase in the injured animals was significantly reduced throughout the cerebral cortex and in 5 of II subcortical structures. This injury-induced depression of oxidative capacity was most pronounced in regions of the hemisphere ipsilateral to the ablation. Animals given D-amphetamine had less depression of oxidative capacity, which was most pronounced bilaterally in the cerebral cortex, red nucleus, and superior colliculus; and in the nucleus accumbens, caudateputamen, and globus pallidus ipsilaterai to the ablation. The ability of D-amphetamine to alleviate depressed cerebral oxidative metabolism following cortical injury may be one mechanism by which drugs increasing noradrenaline release accelerate functional recovery in both animals and humans.